Phase Diagram, and Structural and Electrical Properties of Pyrochlores in Bi2o3-Zno-Nb2o5 Ternary System - Tan, Kar Ban (2007)
A comprehensive investigation of phase diagram, structural and electrical properties of pyrochlores in Bi2O3-ZnO-Nb2O5 ternary system was presented. A thorough and complete literature review was carried out in order to gather background information on bismuth zinc niobate (BZN) phases and related materials. Thus, a better understanding in the phase formation, research problems, electrical and thermal properties of the investigated materials and their potential application is achieved.